The Role Of Leader Improve Patient Safety Culture - Muh Abdurrouf; Nursalam Nursalam; Ahsan Ahsan; Mira Triharini; Dyah Wiji Puspitasari; Retno Issroviatiningrum; Nila Fauziza (Universitas Muhammadiyah Semarang, 2023)
One of the important things that must be considered by the hospital is patient safety, where patient safety can be improved by implementing a patient safety culture, so that the patient safety culture goes well, it is necessary to increase the role of the leader. This study aims to determine whether there is a relationship between the role of a leader and the implementation of patient safety culture. Method: this research is a quantitative study using cross sectional. Data were collected using a questionnaire of 118 nurses using a total population sampling technique. The statistical test used is the spearmen rank test. Results: the results of this study are that the majority of the role of leaders is in the good category (92.6%), the majority of patient safety culture is in the good category (90.7%) there is a significant relationship between the role of leaders and the implementation of patient safety culture with a p-value of 0.00 , and r : 0.381, conclusion: Increasing the role of a leader in the form of a decision-making role, interpersonal role, and informational role can improve patient safety culture